Body Orientation Affects the Perceived Size of Objects. (January 2022) - Kim, John J.-J.; McManus, Meaghan E.; Harris, Laurence R.
Here, we investigate how body orientation relative to gravity affects the perceived size of visual targets. When in virtual reality, participants judged the size of a visual target projected at simulated distances of between 2 and 10 m and compared it to a physical reference length held in their hands while they were standing or lying prone or supine. Participants needed to make the visual size of the target 5.4% larger when supine and 10.1% larger when prone, compared to when they were in an upright position to perceive that it matched the physical reference length. Needing to make the target larger when lying compared to when standing suggests some not mutually exclusive possibilities. It may be that while tilted participants perceived the targets as smaller than when they were upright. It may be that participants perceived the targets as being closer while tilted compared to when upright. It may also be that participants perceived the physical reference length as longer while tilted. Misperceiving objects as larger and/or closer when lying may provide a survival benefit while in such a vulnerable position.